Statistical distribution of different cumulative periods of rainfall in Haryana (MAUSAM, 1978)
The statistical distribution of the accumulated rainfall for one, two, three, four, six, eight and sixteen weeks commencing from the onset of the southwest monsoon (25th standard week) have been studied in respect of a low rainfall station, Hissar and high rainfall station, Ambala in the Haryana State. The study of rainfall distribution indicated that upto a cumulative period of four weeks skewness is very high and, therefore, normal distribution cannot be fitted. In such cases gamma distribution has been fitted and found satisfactory. Whereas, beyond four weeks cumulative period, normal distribution has been found satisfactory. Probability charts have been prepared using the theoretical distribution to study their behaviour with respect to crop planning.